Effects of Synbiotics on the Fecal Microbiome and Metabolomic Profiles of Healthy Research Dogs Administered Antibiotics: A Randomized, Controlled Trial - Whittemore, Jacqueline C.; Price, Joshua M.; Moyers, Tamberlyn; Suchodolski, Jan S. (Frontiers in Veterinary Science, 2021)
Background. Antibiotic-associated gastrointestinal signs occurred in 100% of dogs administered enrofloxacin with metronidazole in a previous study, and signs partially were mitigated by synbiotics. The objective of this randomized, double-blinded, placebo-controlled trial was to compare the fecal microbiome and metabolome of dogs administered enrofloxacin and metronidazole, followed by either a placebo or a bacterial/yeast synbiotic combination. Methods. Twenty-two healthy research dogs were randomized to two treatment groups. There were three study periods: baseline, treatment, and washout. Dogs were administered enrofloxacin (10mg/kg qd) and metronidazole (12.5mg/kg BID), followed one hour later by placebo or a commercially-available synbiotic combination (BID), PO for 21 days with reevaluation 56 days thereafter. Fecal samples were collected on days 5-7 (baseline), 26-28, and 82-84. The fecal microbiome was analyzed by qPCR and sequencing of 16S rRNA genes; time-of-flight mass spectrometry was used to determine metabolomic profiles. Split plot repeated measures mixed model ANOVAs were used to compare results between treatment groups. P < 0.05 was considered significant, with Benjamini & Hochberg’s False Discovery Rate used to adjust for multiple comparisons. Results. Alpha diversity metrics differed significantly over time in both treatment groups, with incomplete recovery by days 82-84. Beta diversity and the dysbiosis index differed significantly over time and between treatment groups, with incomplete recovery at days 82-84 for dogs in the placebo group. Significant group-by-time interactions were noted for 15 genera, including Adlercreutzia, Bifidobacterium, Slackia, Turicibacter, Clostridium (including C. hiranonis), [Ruminococcus], Erysipelotrichaceae_g_, [Eubacterium], and Succinivibrionaceae_g_. Concurrent group and time effects were present for six genera, including Collinsella, Ruminococcaceae_g_, and Prevotella. Metabolite profiles differed significantly by group-by-time, group, and time for 28, 20, and 192 metabolites, respectively. These included short-chain fatty acid, bile acid, tryptophan, sphingolipid, benzoic acid, and cinnaminic acid metabolites, as well as fucose and ethanolamine. Changes in many taxa and metabolites persisted through days 82-84. Conclusion. Antibiotic administration causes sustained dysbiosis and dysmetabolism in dogs. Significant group-by-time interactions were noted for a number of taxa and metabolites, potentially contributing to decreased antibiotic-induced gastrointestinal effects in dogs administered synbiotics.